Does The SETS Model Improve Problem Solving Thinking Ability? Meta-Analysis - Nasruddin Nasruddin; Agus Triyono; Siti Aisyah; Fitriah Handayani; Muhammad Edy Nurtamam; Tomi Apra Santosa (Badan Penerbit STIEPARI Press, 2023)
This study aims to determine the effect of the SETS learning model to improve students' problem-solving abilities. This type of research is a meta-analysis. This study analyzed 9 national and international journals published from 2020-2023. Data search through google scholar; IEEE; Frontier Journal; ERIC and Taylor of Francis. Selection of data sources through PRISMA method consisting of Identification, Screening, Eligibility and Included. Data analysis with the help of JSAP software. The results of the analysis of 9 effect sizes concluded that the SETS learning mode had a positive effect on students' problem-solving abilities with (z = 6.187; p < 0.001). This finding explains that the SETS learning model has a significant effect on problem-solving ability with high categories ( rE = 0.876). The SETS learning model is effective for teachers to develop in encouraging students' solving skills in learning.